Answer:
Distance = 4 units
Step-by-step explanation:
Points:
(-1,-6) and (3,-6).
Solution:
We will use Distance formulae,
[tex] \rm \: D= \sqrt{(x_2 - x_1) {}^{2} + (y_2 - y_1) {}^{2} } [/tex]
- [tex] (x_2,x_1) = (3,-1)[/tex]
- [tex](y_2,y_1) = (-6,-6)[/tex]
Substituting,
- [tex]\rm D = \sqrt{ \{(3 - ( - 1) \} {}^{2} + \{( - 6) - ( - 6) \} {}^{2} } [/tex]
- [tex]D = \sqrt{(3 + 1) {}^{2} + \{ - 6 + 6 \}^2 } [/tex]
- [tex]D = \sqrt{4 {}^{2} + 0 {}^{2} } [/tex]
- [tex]D = \sqrt{16} [/tex]
- [tex]D = \sqrt{4 \times 4} [/tex]
- [tex] \rm \: D = 4[/tex]
Distance is 4 units.